The impact of structures and processes on intergovernmental processes in the Sol Plaatje Municipality - Ntsenge, Buhle (University of the Free State, 2020)
When the Constitution of the Republic of South Africa, 1996 (Act 108 of 1996) came into operation on 4 of February 1997, it represented the historical culmination of a focused process of constitution-writing which commenced in December 1991. This process came as a result of the initiation of the Convention for a Democratic South Africa (CODESA), a national multi-party constellation established to negotiate a transition to inclusive democracy (Venter, 2014: 2). Groups or individuals cannot exist without regulations or laws. Even when these laws are put in place, there is a need to implement and govern them, hence the need for a body or structure that will oversee the adherence to these rules and regulations: a constitution. This constitution is the supreme law of the Republic; law or conduct inconsistent with it is invalid, and the obligations imposed by it must be fulfilled (Ngcukaitobi, Brickhill, & Stein, 2012: 319). Chapter 3 of the Constitution of South Africa sets out the principles of Cooperative Governance; all spheres must observe and adhere to the principles in this chapter and must conduct their activities within the parameters that the chapter provides (Mhone & Edigheji, 2003: 156). Intergovernmental Relations begin to have importance where there is a separation of powers amongst different spheres of government (Ismail, Bayat & Meyer, 1997: 138). South Africa has three spheres of government, namely national, provincial, and local (municipal). National government is then divided into three branches: law-making (legislative authority), the actual operations of governing (executive authority), and the courts (judicial authority). All these structures of government are interdependent and need each other to function and to operate effectively. This practice is known as Intergovernmental Relations. Intergovernmental Relations (IGR) is defined as the processes and institutions through which governments within a political system interact (Phillimore, 2013: 229). These institutions function as interacting networks of institutions at all levels; they are created to enable the various parts of government to form a unified whole, with cooperative governance playing a larger role as it derives mandate from the constituency at regional levels (Phillimore, 2013: 229). Ismail et al (1997: 139) asserts that cooperative governance is a new idea to resolve issues associated with Intergovernmental Relations seeking to address the difficulties pertaining to the coordination of government functions and streamlining of government’s administrative responsibilities (Ismail et al., 1997: 139). The value of Intergovernmental Relations in South Africa is evident with the integration of local government and traditional affairs as the defining element of cooperative governance. cooperative governance alludes to all types of government that adopt political flexibility, negotiation, compromise, and less reliance on the rigid distribution of powers between the three spheres of government (Tau, 2015: 801). The powers and authority of local government with its mandate to regulate its own laws and matters pertaining to its jurisdiction is recognised by the Constitution in South Africa. Section 151 (4) of the South African Constitution states that national and / or provincial government spheres may not compromise or prevent the functions of local government (Ismail et al., 1997: 139). 𝗥𝗘𝗙𝗘𝗥 𝗧𝗢 𝗧𝗛𝗘 𝗔𝗧𝗧𝗔𝗖𝗛𝗘𝗗 𝗗𝗢𝗖𝗨𝗠𝗘𝗡𝗧 𝗙𝗢𝗥 𝗔 𝗙𝗨𝗟𝗟 𝗦𝗨𝗠𝗠𝗔𝗥𝗬! ___________________________________________________________________
Dissertation(M.A.(Governance and Political Transformation))--University of the Free State, 2020
Keywords: Constitution of the Republic of South Africa, 1996; Convention for a Democratic South Africa (CODESA); Intergovernmental Relations; Cooperative Governance; National government; Provincial government; Provincial government; Local government